DESIGN AND SELECTION OF COMPETITIVE STRATEGY IN PT. ELNOV DWIATA MANDIRI WITH SWOT METHOD AND COMPLEX PROPORTIONAL ASSESSMENT - Akbar, Mohammad; Nugraha, Qori (Barometer, 2024)
Elnov Dwiata Mandiri is a Company engaged in electrical maintenance servies. This company operates on a project basic where the process is carried out if there is a request by a service user or client. This company is a company with project model that must have high adaptation and respond to the surrounding environment. Therefore, the argument is strengthened tha existence of strategic planning is an important topic. This research was conducted with the aim of knowing internal and external environmental factors using the IFE and EFE matrices and looking for alternative strategies using the SWOT matrix and determining competitive strategies based on appropriate criteria using Complex Proportional Assessment (COPRAS). The results showed that IFE matrix value was 3,18 and the EFE matrix value was 3,69. If depicted in the IE matrix, the company’s condition is in quadran I, which means a build and growth strategy to improve good relations with distributors and suppliers, and improve the structure company. Strategy by improving the quality of Operatonal HR is the best alternative strategu to be implemented at PT. Elnov Dwiata Mandiri with a utility values of 100%. This strategy is the most appropriate to implement so that human resources are more productive at work and to create positive changes for emloyees